PEMBERDAYAAN PETANI MELALUI PELATIHAN PENGOLAHAN BERAS MENJADI TEPUNG BERAS SEBAGAI BAHAN PANGAN OLAHAN ANEKA KUE DI KECAMATAN BIKOMI UTARA KABUPATEN TIMOR TENGAH UTARA - Mardit Nikodemus Nalle; Meri Helsiana Mata; Febrya Christin Handayani Buan; Josua Sahala (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tunas Pembangunan Surakarta, 2026)
The concept of Entrepreneurship is needed for the community to increase farmers' income for the community so that a strong push is needed for the community to seize opportunities in the border areas of Indonesia and Timor Leste. The Melati Women Farmers Group of Haumeni Village became a threshing area in an effort to mobilize group members in developing Entrepreneurship through training in processing local products made from rice flour into other local foods to be made into local specialties which can later become regional souvenirs. For this reason, strong training is needed both from processing methods, how to utilize the technology used and how to manage the business in order to increase income and in the future can expand the scale of the business. The problem approach that will be formulated in developing Farmer Empowerment activities in North Bikomi District for the Haumeni Women Farmers Group is: Socialization, Scheduling and Training and Programs. The conclusion of the farmer group can increase knowledge in processing raw materials into processed foods that have high added value. Local processed food products have high economic value in increasing the profits of farmers and women's farmer groups from the production results which can later be sold either at their own outlets or through collaboration with shops or other kiosks